Using (U-234/U-238) to assess diffusion rates of isotope tracers in ferromanganese crusts - Henderson, G; Burton, K (1999)
Ferromanganese crusts record seawater isotope history for several elements useful for paleoceanography. Interpreting crust isotope profiles, however, requires an assessment of the rate of diffusion of each element within the crust. We address this issue using U- and Th-isotope profiles, coupled with concentration measurements of some trace elements whose isotopes are often measured in crusts. A depth profile of (230Th(xs)/234U) for a North Atlantic crust (Alv539) yields a growth rate of 3.05 mm/Myr, consistent with an existing 10Be/9Be record. But the growth rate implied by a (234U/238U) profile in the same crust is ~6 times faster due to diffusion of U in the crust. The difference between the observed (234U/238U) profile and that expected from (230Th(xs)/234U) enables the effective diffusivity of U to be calculated as 1.2 x 10-6 cm2/year. Recalculated literature data indicate that other crusts have diffusivities which range down to 4.7 x 10-8 cm2/yr. This variation is to be expected given the range of porosity observed for ferromanganese crusts. Concentration measurements of various elements in the surface layer of the crust provide relative distribution coefficients for each element between seawater and crust. These distribution coefficients enable the effective diffusivity of each element to be calculated by comparison with the diffusivity of U. Such diffusivities are assessed for crust Alv539 and give a first indication of the expected preservation of isotope signals in ferromanganese crusts. Li, Os, and Sr have diffusivities of 2 x 10-4, 3 x 10-5 and 2 x 10-5 cm2/year respectively and diffusion is expected to be sufficiently fast that crusts will not accurately preserve past seawater compositions. Th, Nd, Pb and Be have diffusivities less than 10-9 cm2/year and are highly immobile in crusts, a reassuring result for Th and Be crust chronologies and for Nd- and Pb-isotope tracing of past water masses using crusts. Hf has a diffusivity of 3 x 10-8 in Alv539 - fast enough to perturb but not destroy its isotope history. For studies of Hf in this and other crusts, diffusion should therefore be considered. Measuring U-isotope profiles provides a potential way of assessing such diffusion for Hf or for other elements with relatively low distribution coefficients into ferromanganese crusts.